2011
DOI: 10.4269/ajtmh.2011.11-0194
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Molecular Markers of Antimalarial Drug Resistance and Relationship with Artesunate-Mefloquine Combination Therapy in Patients with Uncomplicated Plasmodium falciparum Malaria in Thailand

Abstract: Abstract. The aim of this study was to investigate the association between genetic polymorphisms of Plasmodium falciparum chloroquine resistance transporter ( pfcrt ), P. falciparum multidrug resistance 1 ( pfmdr1 ), and P. falciparum ATPase ( pfatp6 ) and clinical outcome after a three-day mefloquine-artesunate combination therapy in 134 patients with uncomplicated Plasmodium falciparum malaria in an area with multidrug resistance along the Thailand-Myanmar border. Analysis of gene mutation and amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…The prevalence of pfmdr1 amplification was relatively low (12-19%) across the three border regions included in the current study; and only a single isolate had a CN of three or more. Results from Karen State contrast with recent studies documenting elevated CN in at least 40% of isolates [9] with a mean CN of 2.9 (SE 1.4) [39] among refugee, migrant and cross-border populations in Thailand (Figure 1). Findings from Kachin State contrast with a recent study in Laiza that found no pfmdr1 amplification in 171 P. falciparum isolates [40,41], but is consistent with a study conducted in 2004 in nearby counties of Yunnan province [42].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The prevalence of pfmdr1 amplification was relatively low (12-19%) across the three border regions included in the current study; and only a single isolate had a CN of three or more. Results from Karen State contrast with recent studies documenting elevated CN in at least 40% of isolates [9] with a mean CN of 2.9 (SE 1.4) [39] among refugee, migrant and cross-border populations in Thailand (Figure 1). Findings from Kachin State contrast with a recent study in Laiza that found no pfmdr1 amplification in 171 P. falciparum isolates [40,41], but is consistent with a study conducted in 2004 in nearby counties of Yunnan province [42].…”
Section: Discussioncontrasting
confidence: 95%
“… Systematic review of in vivo , in vitro , and molecular resistance studies in Myanmar and neighbouring countries, 1996–2009 [ [1,7,9,10,13,39,40,60-82] ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to pfmdr1 copy number, the increase of copy number found in some P. falciparum isolates in this study correlates well with the observation of decline in sensitivity of P. falciparum to artesunate and mefloquine and therefore, the chance of recrudescence/treatment failure following treatment with this artemisinin-based combination therapy regimen [25,26] . Application of the median copy number and prevalence of isolates carrying more than one gene copies can sort out the provinces with relatively high possibility of treatment failure and require close monitoring for drug resistance as Kanchanaburi, followed by Mae Hongson, Tak and Ranong, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Although polymorphisms at the pfmdr1 codons 86, 184, 1034, 1042, 1246 are associated with altered sensitivity to artemisinins and mefloquine in SEA, the key determinant has been shown to be the copy number variation ( Cowman et al., 1994; Price et al., 1999; Duraisingh et al., 2000; Price et al., 2004; Sidhu et al., 2005; Picot et al., 2009; Muhamad et al., 2011 ). Further, the discovery of mutations in K13-propeller in SEA but not in African parasites shows the multigenetic nature of artemisinin resistance in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%